Impact of polyunsaturated fatty acids on patient-important outcomes in children and adolescents with autism spectrum disorder: A systematic review - De Crescenzo, F; D’Alò, GL; Morgano, GP; Minozzi, S; Mitrova, Z; Saulle, R; Cruciani, F; Fulceri, F; Davoli, M; Scattoni, ML; Nardocci, F; Schünemann, HJ; et al. (Springer, 2020)
Background: Recent randomized controlled trials (RCTs) claimed PUFAs to be effective for autism spectrum disorder (ASD) but international guidelines have not considered yet this body of evidence. Our aim was to assess the effectiveness of PUFAs in children and adolescents with ASD, for the Italian national guidelines on the management of ASD in children and adolescents.